Annual Plan 1998-99 Draft Proposals Volume II Government of Meghalaya - Planning Commission (Planning Commission, 1998)
The economy of Meghalaya is basically agrarian and rural with agriculture playing a oredominant role in the State’s economy. The progress rhe Agriculture sector, however, continued to be handicapped due to slow changing cf old memods/technology and large scale shifting cultivation (.Jhun ing) which resulted in fluctuating agriculture p;-declivity. The cultivated area of the state is about 10% of the total geographical area on average during the past 5 yeais. the gross cropped area is 2.60 lakh hectare while the net cropped area is 2 16 lakh hectares in 1996-97. A target of gross cropped area of 1. 79 lakh hectares and net cropped area 2. 38 lakh hectares is proposed for the year 1998-99- against the anticipated gross cropped area of 2. 77 lakh hectares during 1997-98.
Planning Department Government of Meghalaya